Risse in der geoökologischen Realität.: Chaos und Ordnung in geoökologischen Systemen - Kempel-Eggenberger, Christa (ERDKUNDE, 1993)
Complexity provides the fundamental problem in modelling a geoecosystem. The problems discussed in this paper concern the methods of traditional complex site analysis with its conceptual model Standortregelkreis, the basic tool within landscape analysis. Objects in question are transport and changeover of solutes in the test-area HFJ. First results show the schismatic character of geoecological reality as not being represented in the model. The geoecological model discussed takes the theory of attaining steady states as a basis. Statistical characteristics and site balances help to approach this normal deterministic-mechanistic dynamic of geoecosystems here visualized in the regularity of seasonal cycles. Focusing events and scenarios offer an opposite reality. Discontinuity of solute transport and chaotic behaviour far from equilibrium are emphazised. Time series characteristics which obviously sign complexity make single events singular. A steady succession of phases with different correlation structure not being included in the model makes the real deposition situation and stability of the HFJ test-area uncertain. Chaos theory established phase-space analysis, which is supposed to solve this methodical and real conflict of space and time. Even most simple two dimensional phase-space pictures constructed on HFJ data show additional information on the complexity of solute transport. Serious data processing with phase-space techniques is believed to lead the deadlocked process-correlation model Standortregelkreis to a handy basis far a future simulation model to work with in geoecology.